Legal Protection of Vulnerable Consumers in Digital Transactions in Indonesia - Dewi Nadya Maharani; Muhamad Afifullah; Fauzan Muzakki; Henni Wijayanti; Roosdiana Harahap (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid growth of e-commerce, fintech, and digital platforms has transformed consumer interactions while increasing consumer risks in the digital economy. Specific Background: Consumer protection in Indonesia is governed by the Consumer Protection Law and supported by the Electronic Information and Transactions Law, the Personal Data Protection Law, and sectoral regulations related to electronic systems. Knowledge Gap: Despite these regulations, legal fragmentation creates uncertainty and fails to explicitly recognize vulnerable consumers in digital transactions. Aims: This study develops a conceptual framework for vulnerable consumers and examines its incorporation into Indonesia’s Consumer Protection Law. Results: The findings reveal that Indonesia’s legal framework remains formally equal and fragmented, providing only partial protection through sectoral regulations while leaving many vulnerable groups insufficiently protected. Novelty: The study integrates theories of legal protection, distributive justice, the welfare state, and consumer rights to propose a vulnerability-sensitive framework. Implications: The findings support the harmonization of consumer protection, electronic transaction, and personal data protection laws to establish a more adaptive and inclusive consumer protection system in Indonesia’s digital ecosystem. Highlights: Indonesia’s consumer protection regime does not explicitly recognize vulnerable consumers in digital transactions. Regulatory fragmentation creates legal uncertainty and protection gaps. Legal harmonization is needed to support an inclusive digital consumer protection framework. Keywords: Legal Protection, Vulnerable Consumers, Digital Transactions